Faktor Khauf : Bagaimana Peran Khauf dalam Memoderasi Sikap pada Kecurangan terhadap Integritas Akademik - Darsih; Fadhilah Suralaga (Program Studi Psikologi Islam, Fakultas Psikologi, Universitas Islam Negeri Raden Fatah Palembang, 2024)
Previous research has explored various strategies for promoting academic integrity (AI); however, there is a gap in understanding how religious behavior, particularly the concept of khauf (fear of God), can be investigated as a factor influencing and moderator toward academic integrity. Therefore, this study aimed to analyze whether khauf moderates the influence of attitude toward cheating (ATC) on academic integrity. Using the PLS-SEM analysis method, the questionnaire was distributed through cluster random sampling to 224 students of Islamic colleges in Jakarta, Tangerang, and Bekasi. The results showed that the fear of God (khauf) can moderate the influence of attitude toward cheating (ATC) on academic integrity, with a significance p-value of 0,002. Integrating religious values such as khauf may be a valuable approach to strengthening academic integrity in educational institutions. The practical implications of this research were the need to consider strategies that emphasize religious moral values as an essential element in building an integrated academic culture, one of which is the fear of God (khauf